Model Konseling Berorientasi Hipnosis untuk Meningkatkan Kebahagiaan pada Mahasiswa - Anggita, Sahira; Arumsari, Cucu; Imaddudin, Aam (Universitas Muhammadiyah Metro, 2024)
Happiness becomes an essential thing in the development of students as individuals who can live a happy college life tend to develop better, be productive, and be successful in their academic studies. A low level of happiness makes students unable to feel positive emotions, it is difficult to have full involvement in doing various things, they lack positive relationships with others, they think that their life is less meaningful, and they think they have less meaningful achievements. This study aims to test the effectiveness of a hypnotic-oriented counseling model to increase happiness in students with low happiness levels. This study used the experimental method of single-subject research with an A-B-A pattern. The population used is students of the Muhammadiyah University of Tasikmalaya class of 2021, with the subjects sampled to be given interventions and students with a low happiness level. The data analysis technique used is a visual analysis by looking directly at the trend line on the graph and statistical analysis using PND (Percentage Non-Overlapping Data) calculations to test the effectiveness of the interventions provided. The results showed that there was a significant increase in the happiness score in the baseline phase (A1), then intervention (B), and baseline (A2). Thus, the hypnosis-oriented counseling model has been proven effective in increasing students' happiness levels with low happiness levels.